Dynamics of Sharia Economic Development: Halal Industry Product Strategy - Aida, Farchati Umu; Imarotul, Salsabila; Khafsoh, Saniatul (Laboratorium Riset Ekonomi, 2024)
This article aims to describe how the halal industry strategy has a significant effect on the dynamics of Islamic economic development. Indonesia also has great potential to develop the halal sector. Certainly, Indonesia's large Muslim population has implications related to this huge potential. Due to the large Muslim population, there is a high demand for halal products. The researcher also noted the opportunities and difficulties in developing the halal industry sector in Indonesia. In an effort to provide deeper insight into the issues mentioned above, researchers attempt to conduct an evaluation of the literature pertaining to the research subject